DMSO enhanced conformational switch of an interfacial enzyme. Issue 12 (22nd September 2016) - Lindsay, Richard J.; Johnson, Quentin R.; Evangelista, Wilfredo; Nellas, Ricky B.; Shen, Tongye
Abstract: Interfacial proteins function in unique heterogeneous solvent environments, such as water–oil interfaces. One important example is microbial lipase, which is activated in an oil‐water emulsion phase and has many important enzymatic functions. A unique aprotic dipolar organic solvent, dimethyl sulfoxide (DMSO), has been shown to increase the activity of lipases, but the mechanism behind this enhancement is still unknown. Here, all‐atom molecular dynamics simulations of lipase in a binary solution were performed to examine the effects of DMSO on the dynamics of the gating mechanism. The amphiphilic α5 region of the lipase was a focal point for the analysis, since the structural ordering of α5 has been shown to be important for gating under other perturbations. Compared to the closed‐gorge ensemble in an aqueous environment, the conformational ensemble shifts towards open‐gorge structures in the presence of DMSO solvents. Increased width of the access channel is particularly prevalent in 45% and 60% DMSO concentrations (w/w). As the amount of DMSO increases, the α5 region of the lipase becomes more α‐helical, as we previously observed in studies that address water–oil interfacial and high pressure activation. We believe that the structural ordering of α5 plays an essential role on gating and lipase activity.